Odnos in znanje medicinskih sester ter ovire pri implementaciji na dokazih temelječe prakse - Bole, Urban (Obzornik zdravstvene nege, 2018)
Introduction: Evidence-based practice is now regarded as the %gold standard% in health care delivery worldwide. The aim of the research was to study the attitudes, knowledge and obstacles in the implementation of evidence-based practice in nursing. Methods: A systematic review of scientific and professional literature was conducted whereby the CINAHL, ProQuest Dissertations & Theses Global, SpringerLink, Wiley and PubMed data bases were used. The search limiting criteria were: the publication of the article between 2008 to 2017 and a complete article text in the English language. The search key words were: nurse, evidence based practice, implementation barriers. 37 articles were included in the final analysis. The assessment of the quality of evidence is shown in the hierarchy of evidence. The data were processed with a thematic qualitative analysis. Results: 73 codes were identified and combined to 7 content categories: (1) factors affecting a negative attitude of nurses towards evidenced-based practice, (2) factors affecting a positive attitude of nurses towards evidencedbased practice, (3) research skills to be able to use scientific evidence in clinical settings, (4) information technology skills to be able to search for scientific evidence, (5) the impact of competencies and mentoring for the implementation of evidence-based practice in clinical settings, (6) barriers of an organization for the implementation of evidence-based practice and (7) barriers of nurses to implement evidence-based practice. Discussion and conclusion: The research has revealed that nurses have positive and negative attitudes towards evidence-based practice. It focuses on the lack of knowledge and the obstacles which nurses encounter in the implementation of evidence-based practice in a clinical environment.
Keywords: barriers; evidence based practice; implementacija; implementation; na dokazih temelječa praksa; nursing; ovire; zdravstvena nega